Breakfast clubs in the Czech Republic: food security, socialisation, education, or participation? The evolution of intervention goals - Jaroslava Simonová; Jana Straková (Humanities & Social Sciences Communications)
Abstract This study examines the implementation of breakfast clubs across all the Czech schools that opted for this intervention under an EU-funded programme aimed at supporting socio-economically disadvantaged students. Schools were given the flexibility to tailor the programme to local needs. Using a combination of inductive and deductive content analysis of school reports, we found a shift in focus from nutrition to broader educational, socialisation, and participatory goals. While the original nutritional objectives were often overshadowed, the adaptations made by schools addressed the broader needs of their students effectively. The findings highlight the importance of balancing fidelity to core goals with adaptability in educational interventions. The lessons learned offer valuable insights for similar programmes in other socio-economically challenged contexts.